Prevalence of two root canals in human mandibular anterior teeth in an Iranian population - Saeed Rahimi; Amin Salem Milani; Shahriar Shahi; Youbert Sergiz; Saeed Nezafati; Mehrdad Lotfi (Wolters Kluwer Medknow Publications, 2013)
Background: Complete debridement and obturation of the root canal system is a key factor in successful endodontic treatment and the operator should therefore have thorough knowledge of the root canal morphology of the teeth. Numerous studies have been carried out to investigate the canal configuration of different tooth types in various populations. Aims: The aim of the present study was to investigate the internal anatomy of mandibular incisors and canines in an Iranian population. Materials and Methods: A total of 463 mandibular anterior teeth, including 186 centrals, 128 laterals, and 149 canines, were examined. A standard clearing technique was used to make the teeth transparent. India ink was injected into the canals of the teeth and the samples were examined with a magnifying glass. The root canal configurations were categorized according to the Vertucci classification. Results: All the incisors in this study had one root, and 12.08% of the canines had two roots. We found a slightly higher prevalence of the second canal in incisors than in canines (36.62% vs. 20.48%). However, the probability of canines having two separate apical foramina was higher than that for incisors (12.08% vs. 0.64%). Conclusions: In view of the high prevalence of two-canaled mandibular anterior teeth found in this study, it would be prudent to assume that any mandibular anterior tooth being treated is two-canaled until a thorough search proves otherwise.